An In Vitro Study Of Immunomodulatory Role Of Tiits In Respect To Cytotoxic Lymphocytes In Four Grades Of Human Glioma - PANKAJ KUMAR,; SAGAR ACHARYA,; SIRSHENDU CHATTERJEE,; ANNPURNA KUMARI,; SUHNRITA CHAUDHURI,; MANOJ KUMAR SINGH,; SAMARENDRA NATH GHOSH,; SWAPNA CHAUDHURI, (International Journal of Pharma and Bio Sciences, 2012)
T11 target structure (T11TS), a membrane glycoprotein has been documented with antineoplastic activity in animal model in our lab. Previously, in animal study we have documented T11TS induced cytotoxic abrogation of tumor cells. Encouraged by these established findings by our group and as prerequisite for clinical trial, this study has been designed to assess the cytotoxic potential of the patient’s lymphocytes in in vitro study of autologous human glioma as modulated by T11TS. Meningioma samples were chosen as disease control group. The data produced indicates T11TS induced up regulation of cytotoxicity of T lymphocytes in grade I and II glioma. Significant enhancement of cytotoxic protein, perforin and granzyme suggest cytotoxic death of T11TS induced target tumor. Also,T11TS downregulates the TGF-β secretion in grade I and II tumor cells. These preliminary findings may help in pushing this molecule into pharmaceutical domain.